Pengaruh Struktur Modal, Kebijakan Dividen, Ukuran Perusahaan terhadap Nilai Perusahaan pada Perusahaan Manufaktur Sektor Industri Barang dan Konsumsi yang Terdaftar di BEI 2016-2020 - Syahla Dewi Lukitasari Millenia; Gendro Wiyono; Pristin Prima Sari (LPPM Institut Nasional Laa Roiba Bogor, 2023)
This study aims to determine the effect of capital structure, dividend policy, firm size on firm value in manufacturing companies in the consumer goods and industrial sector listed on the Indonesia Stock Exchange (IDX) in the 2016-2020 period. In this research, the method used is quantitative data type. Analysis of the data used in this study using descriptive analysis, classical assumption test, multiple linear regression test, hypothesis testing, and determinant coefficient test assisted by the SPSS program. In taking the sample of this study using purposive sampling method. Thus, the sample obtained was 15 companies that had met the research criteria and 75 data were collected for 5 years. The results of this study indicate that the capital structure has a negative and insignificant effect on firm value. Dividend Policy has no negative effect on Firm Value. However, the firm size variable has a positive and significant effect on firm size. Keywords: capital structure, dividend policy, firm size, firm value